Understanding health information literacy of mHealth app users from digital wellbeing perspective : evidence from regression analysis and fsQCA - Fu, Shaoxiong (2021)
While past research suggests mHealth apps help cultivate users’ health information literacy (HIL), factors contributing to their HIL development have not been systematically studied. Applying digital wellbeing framework, an empirical investigation using a large-scale survey dataset was conducted. From regression analysis and fuzzy-set qualitative comparative analysis (fsQCA), two findings were yielded. First, six influential factors, including person-specific factors (i.e., gender, annual family income, Internet experience), device-specific factors (i.e., screen sizes of mobile phones), and context-specific factors (i.e., use frequency and perceived quality of mHealth apps), were identified. Second, gender, annual family income, internet experience, screen size of mobile phones, use frequency and perceived quality of mHealth apps had synergistic effects on HIL. By introducing fsQCA to library and information science community, the study not only extends literature by teasing out the combinations of different categories of factors contributing to HIL but informs health professionals and mHealth app developers.